Justice collaborator status in murder based on Law Number 31 of 2014 - Hakim, Luqmanul; Hermansyah, Erwin Owan; Sulastri, Lusia (International Journal Labs, 2023)
Provisions regarding Justice Collaborator are regulated in Law Number 31 of 2014 concerning the Protection of Witnesses and Victims. In practice, it is not uncommon for the role of Justice Collaborator to be applied inappropriately. For example, in the case of Bharada Richard Eliezer Pudihang Lumiu. This study aims to examine and analyze the determination of justice collaborator according to Law Number 31 of 2014 and examine and analyze the ideal construction of determining the status of justice collaborator for perpetrators of premeditated murder crimes. This study uses normative juridical research with secondary data in the form of primary, secondary, and tertiary legal materials. The results showed that the determination of the status of justice collaborator in the Brigadier Joshua murder case by the defendant Ricard Eliezer the application for Justice Collaborator status should have been rejected by the panel of judges, where the crime of premeditated murder was not included in the category of cases that qualified as Justice Collaborator based on the provisions of Law Number 31 of 2014, but for the sake of disclosure of the case, and in order to fulfill the responsibility of judges in carrying out their main duties and functions, to enforce the law optimally in order to fulfill a sense of justice, expediency and legal certainty. The Justice Collaborator system for premeditated murder perpetrators requires clearer, more detailed legal rules, as per the rule of law, legality, and certainty theories, compared to arrangements in America, Italy, and Hong Kong.